Effect of FTY720 treatment on macrophage polarization and its impact on the alveolar bone repair process - Tabanêz, André Petenuci (2018)
The alveolar bone repair process may be influenced by several local and systemic factors that include mediators and immune system cells. Among these cells, macrophages are essential to trigger the repair process, and may acquire an inflammatory (M1) or anti-inflammatory and pro-reparative profile (M2). In this context, we evaluated the effects of FTY720 on macrophage polarization towards the M2 profile and its effects on the alveolar bone repair process. In this study, we used 8 weeks old male C57BL / 6 mice (N = 5 / time / group). The animals were divided in FTY720 group receiving the drug orally at a dose of 3mg / kg / 24h during the whole experimental period, and the control group receiving only the equivalent vehicle. All animals were submitted to extraction of the right upper incisor and were evaluated at 0, 1, 3, 7 and 14 days after extraction, followed by computed tomography (CT), histomorphometry, birefringence, immunohistochemical and molecular analyzes (PCRArray). Our results demonstrated that in the 14-day period, the FTY720 group presented higher bone tissue density, higher bone tissue volume (BV), greater tissue volume fraction (BV / TV), greater number and thickness of trabeculae (Tb.1 and Tb.Th, respectively) (p<0.05). In the 14-day period, the FTY720 group had a higher number of osteoblasts and osteoclasts than the control group (p<0.05). Accordingly, the expression of various bone markers such as BMP2, BMP7, ALPL, SOST and RANK had their mRNA expressions increased in the FTY720 group. This increase may be related to the potentiation in the formation of the bone tissue compared to the control group. The levels of FIZZ, ARG2 and IL-10 mRNA increased in the FTY720 group together with the presence of CD206 + cells in the 14 days period, suggesting a participation of M2 macrophages in the potentiation of the alveolar bone repair process. The FTY720 group also showed increased expression levels of CCR2, CCR5, CXCR1, CXCL1, CXCL3, CCL20 and CCL25 mRNA, chemokines and chemokine receptors involved in the recruitment of inflammatory cells and undifferentiated mesenchymal cells (MSCs) most notably was the up CXCL12 up regulation (p<0.05). CXCL12 is responsible in the recruitment of MSCs to the repair site. The increase in CXCL12 expression was accompanied by an increase in CD34 expression over a period of 14 days (p<0.05), indicating a higher presence of MSCs in the repair site. Thus, our results demonstrate that FTY720 favored the process of alveolar bone repair in C57BL / 6 mice, possibly because it increased the expression of markers related to bone tissue development (ALPL, SOST, RANK), tissue repair (CXCL12, CD34) and inflammatory cells (CCR2, CCR5) and apparently in the induction of macrophages to an M2 profile (ARG2, FIZZ).